Optimizing the Performance of the Sidoarjo Police Bhabinkamtibmas through Sambang to Prevent Criminal Acts of Theft by Increasing Awareness - Gunawan, Andi Muh. Asyraf (Indonesian Journal of Police Studies, 2024)
In the jurisdiction of the Sidoarjo City Police Station (Polresta Sidoarjo), aggravated theft remains one of the conventional crimes that frequently occur. In order to halt cases of aggravated theft, Bhabinkamtibmas in the Sidoarjo City Resort must engage in preemptive efforts through visits. The visitation process conducted by Bhabinkamtibmas of the Sidoarjo City Police Station (including the Sidoarjo Kota, Candi, and Buduran districts) has generally been effective but not yet fully optimal. Data collected from the Criminal Investigation Unit (Sat Reskrim) of the Sidoarjo City Police Station shows that the number of aggravated theft cases in the jurisdiction of Polresta Sidoarjo has fluctuated over the past four years. As a result of this situation, the author decided to conduct further research on the topic of 'Optimizing the Performance of Bhabinkamtibmas of the Sidoarjo City Police Station through Visits in Preventing Aggravated Theft Crimes. The chosen research approach is qualitative and case study research, meaning the Author positions themselves as the research subject who directly engages in fieldwork during the research process. Additionally, this research is supported by data collection techniques including observation, interviews, and documentation studies through documents, with the collected data being validated for accuracy through triangulation. The data is then subjected to data reduction, data presentation, and conclusion determination. The research findings are subsequently examined and analyzed using management theory and Resource theory with concepts of Optimization, Visitation Concept, and Curat Concept. The research findings indicate that Bhabinkamtibmas in Polresta Sidoarjo conducted visits less optimally, resulting in an increase in aggravated theft cases. Internal and external factors are some of the reasons for the unsuccessful activities of Bhabinkamtibmas. Therefore, the researcher suggests that the staff members pay more attention to their duty shifts and maximize the performance of Bhabinkamtibmas.